Affordability of properties on the Wrocław real estate market - Głuszczuk, Dariusz (Przystępność cenowa mieszkań na wrocławskim rynku nieruchomości, 2024)
Aim: To capture changes in the affordability of properties at their purchase on the primary and secondary Wrocław real estate markets in the years 2013-2022. Methodology: Studies into the affordability of properties are conducted using the traditional approach (quantitative indicators), the behavioural approach (e.g. questionnaires), and the extended approach (quantitative indicators and qualitative criteria). This analysis follows the traditional approach. To measure the affordability of properties, the income method was used by constructing an indicator based on the average monthly gross income, property size and average prices per square metre of properties in transactions on the primary and secondary real estate markets using a variant approach, i.e. dependent on the area of liveable space.Results: In the years 2013-2022 on the primary and secondary real estate market there was no tendency indicating a systematic improvement or worsening in the affordability of properties for Wrocław inhabitants. Comparing the data from the years at either end of the analysis (2013, 2022), the affordability of properties in Wrocław improved on the primary real estate market and worsened on the secondary market. Regardless of these changes, it should be noted that the prices of properties in relation to the average gross income is not favourable, limiting potential buyers to the wealthy. Implications and recommendations: Meeting consumer housing needs on the basis of ownership rights does not resolve Wrocław’s housing problems. The limited affordability of properties in purchase transactions clearly indicates the need for additional action to be taken to support the construction of social housing and the development of the commercial rental property market. Originality/value: Traditionally, research into the affordability of property usually focuses on the average income of the population and the average prices of properties calculated per square metre, or the medians of these figures. These approaches ignore the influence of property size on its affordability. The proposed indicator eliminates this shortcoming. Assessment of the affordability of property on the Wrocław real estate market is one of the bases for shaping local housing policy.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 12-20
Keywords: Dolny Śląsk